Strategi Pembelajaran Tahfidz Al-Qur'an dalam Meningkatkan Kualitas Hafalan Santri di Pesantren - Sita Arifah Richana; Satria Budi, M. Hanif (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2022)
The purpose of this study was to analyze (1) How is the hifdzil jadid learning strategy in improving the memorization quality of students in PPTQ Lubabul Fattah and PP Bustanu Usyaqil Qur'an Tulungagung? Fattah and PP Bustanu Usyaqil Qur'an Tulungagung ?, and (3) What is the strategy of muraja'ah hifdzil qadim in improving the memorization quality of students in PPTQ Lubabul Fattah and PP Bustanu Usyaqil Qur'an Tulungagung ?. This research method uses qualitative research with a phenomenological approach and the type of research is field research. Collecting data using interviews, non-participant observation, and documentation. The results showed that (1) the hifdzil jadid learning strategy in improving the quality of memorizing students was memorizing using the tahfidz method, and using the talaqqi method, (2) the muroja'ah hifdzil jadid strategy in improving the quality of students' memorization was muroja'ah using the takrir method. , sorogan muroja'ah using the talaqqi method, holding mudarosah activities with sima'an among students, (3) the muroja'ah hifdzil qodim strategy in improving the memorization quality of students is independent muroja'ah using the takrir method, sorogan muroja'ah hifdzil qodim with the method talaqqi, sema'an routine and evaluation.